Denying psychological properties of girls and prostitutes: The role of verbal insults - Rubini, Monica (2017)
This study examines the negative stereotypes of the category of women and their subcategories through the language of insults. Participants produced a list of epithets induced by the same hypothetical scenario in which the protagonist was presented either as a 'prostitute' or as a 'girl' (i.e., nonprostitute). Findings showed that the prostitute was addressed with taboo-related insults exaggerating sexual behavior, whereas the girl was mainly given warnings and intellectual insults. The implications of these results are discussed in relation to the underlying processes.